Sosialisasi Dan Pengembangan Sumber Daya : Studi Kasus Di Desa Petanang - Indra, M; Pramudita, Syndy; Cincen; Habibah, Sinta; Hendarmin, Rum; Halin, Hamid; Ardiwinata, Yogie (Journal Of Human And Education (JAHE), 2024)
This community service activity was carried out by KKN-T students from Universitas Indo Global Mandiri in Petanang Village, aimed at developing human resources and enhancing the economic skills of the local community. The program focused on active community participation in training and education to utilize local potential, particularly in MSMEs and digital technology use. The participatory method was employed, involving the community in every phase of the activity, from problem identification to evaluation. The results show an increase in the community's capacity, especially among women, to more effectively utilize natural and human resources. Additionally, the collaboration between students and the community went smoothly, creating an inclusive and empowering environment. Through a dialogic and interactive approach, this activity is expected to have a long-term impact on the economic and social independence of the Petanang Village community.